Pengaruh Refugia Kacang Panjang (Vigna unguiculata) dan Bunga Telekan (Tagetes erecta) Terhadap Populasi Musuh Alami dan Hama pada Padi Organik - Zainal Abidin (Universitas Islam Raden Rahmat, Malang, 2021)
ABSTRACT The aim of this study was to determine and analyze the effectiveness of long bean refugia (Vigna unguiculata) and Telekan flower (Tagetes erecta) against the Important Value Index (INP) and diversity of natural enemies and pests in organic rice. This research was conducted from July to September 2021 in the organic rice fields of Sumberngepoh Village, Lawang District, Malang Regency. The technique of observing natural enemies and pests is direct observation (visual control) on refugia and control plants.. The results of observations and analysis showed that the total visits of natural enemies and pests were 12.279 individuals with details of 9 orders namely Araneae, Coleotepra, Diptera, Hemiptera, Hymenoptera, Lepidoptera, Mantodea, Odonata, and Orthoptera with 40 families. The Important Value Index of dominant natural enemies in telekan flowers were Formicidae (67,21%), Sryphidae (50,26%), Dhroshophiladae (20,12%), Muscidae (15,20 %), dan Aphididae (12,27%) the result is high diversity index (3,05). Meanwhile, the Important Value Index of long bean pests, namely Aphididae (12,27%), Acrididae (8,27%), Alydidae (7,26%) had a moderate diversity (2,05). Index. Telekan flowers are able to have a significant impact in inviting several natural enemies, besides telekan flowers with various flower colors are able to increace the aesthetic value in organic rice fileds. Keywords: telekan flowers, long beans, natural enemies ,and pests.